Economic evaluation of a stand alone pv system for a residential household in Malaysia - Appadu @ Applasamy, Vigneswaran (2008)
The price of crude oil has risen from a low of US$ 2 per barrel to a high of US$ 92.40 (as at 1st February 2008). This resulted in searching for an alternative energy source. Since Malaysia lies entirely in the equatorial region with an average daily solar radiation of 4,500kWh/m2, with sunshine duration of about 12 hours, solar photovoltaic system is applicable to be used as an alternative primary energy to replace the conventional system. The purpose of this study is to investigate the cost per kilowatt hour for a stand-alone photovoltaic system supplying energy to a typical household of four applying life-cycle costing (LCC) method of analysis. RETScreen software is used to determine cost of developing a stand-alone photovoltaic system while taking into account the cost per watt of the photovoltaic cells, efficiency and all factors contributing to the output power generated from these cells while doing likewise to the balance of the system which includes the battery storage, charge controller and inverter. The temperature and irradiation effect towards the out power is interpreted using RETScreen. These data are obtained form the Meteorological Department in Petaling Jaya. The effects of which towards the various photovoltaic technologies are thoroughly studied. LCC is applied to determine the cost per kilowatt hour of energy generated more accurately taking into consideration the inflation and interest rates for the next 25 years. With this, a more reliable cost comparison between the cost of energy generated from stand-alone photovoltaic system and power supplied from Tenaga Nasional Berhad can be compared. From this investigation, although stand alone photovoltaic system provides several advantages from the environmental point of view, the major drawback is the fact that it costs ten times more than the cost of conservative energy. The price of energy for a standalone photovoltaic system ranges from RM 5.20/kWh for cadmium telluride to RM 5.32/kWh for amorphous silicon with an average of RM 5.26/kWh taking into account all five PV technologies.